Periodicity and intimations of a Judaic universe in David Mamet’s Faustus - Safaei, Mohammad (International Journal of English Studies, 2018)
David Mamet’s Faustus presents a complex amalgam of various ideas, traditions and cultures. After a preliminary discussion, in this essay, on the adaptive status of Mamet’s Faustus and on the myth of Faustus throughout history, I approach the notion of periodicity and time in the play, in its religious and anthropological contexts. I further investigate the same theme in tandem with the Nietzschean doctrine of eternal recurrence and its intersection with Judaism and, in specific, with Jewish philosopher Soloveitchik’s conception of halakhic man and its antithetical selves, namely cognitive man and homo religiosus. Exploring the echoes of Jewish existentialism in the works of Soloveitchik, I argue that the play, which is categorized as a typical adaptation of Marlowe’s Doctor Faustus, posits serious questions as to human existence and the significance of intellectual negation and spiritual challenge within a Judaic universe. The essay, beyond the analysis of intertextuality in Mamet’s Faustus, tends to underscore the play’s distinguished contribution to the myth of Faustus from a Judaic perspective.